2017
DOI: 10.1039/c7cy00309a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic CoPt nanoparticle-decorated ultrathin Co(OH)2 nanosheets: an efficient bi-functional water splitting catalyst

Abstract: Magnetic CoPt bimetallic NPs anchored on ultrathin Co(OH)2 nanosheet arrays functioned as an efficient bi-functional water splitting catalyst where the intrinsic magnetism of CoPt was used to improve the stability further by providing external magnetic support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 59 publications
2
33
0
Order By: Relevance
“…24 Moreover, the magnetism supported CoPt@Co(OH) 2 arrays showed the improved stability and better hydrogen evolution reaction (HER) characteristics as a result of the intrinsic magnetic property of the catalyst for over all water splitting. 25 All of the above studied metal oxides show good magnetic properties along with good photocatlytic water splitting activity. Hence, we perform a comparative study of the pristine GO and rGOs that reduced by ascorbic acid (rGO-AA) and lemon (rGO-lemon) with respect to their magnetic properties and hydrogen generation to establish the relationship between magnetism and water splitting.…”
mentioning
confidence: 96%
“…24 Moreover, the magnetism supported CoPt@Co(OH) 2 arrays showed the improved stability and better hydrogen evolution reaction (HER) characteristics as a result of the intrinsic magnetic property of the catalyst for over all water splitting. 25 All of the above studied metal oxides show good magnetic properties along with good photocatlytic water splitting activity. Hence, we perform a comparative study of the pristine GO and rGOs that reduced by ascorbic acid (rGO-AA) and lemon (rGO-lemon) with respect to their magnetic properties and hydrogen generation to establish the relationship between magnetism and water splitting.…”
mentioning
confidence: 96%
“…Its corundum-type crystalline structure belongs to the D 3d 6 group for which seven Raman-active modes (2 A 1g + 5E g ) and six IR-active modes (4E u + 2 A 2u ) are expected from symmetry considerations. [50] Namely, the peaks in the lower wavenumber region of the Raman spectra at 224, 242, 290, 406, 487, 606 cm À 1 correspond to A 1g ( 1), E g (1), unresolved [51] E g ( 2) + E g (3), E g (4), A 1g (2), and E g (5) Raman modes, [52] respectively. Besides these peaks', other spectral features in the higher wavenumber region can be seen: peaks at 655 and 808 cm À 1 and a series of bands in the range 950-1700 cm À 1 with the most prominent peak centred at 1310 cm À 1 .…”
Section: Resultsmentioning
confidence: 99%
“…At present, tremendous strategies have been applied for enhancing the stability of catalysts or electrodes for HER and OER, but for TM(OH)x, which exhibited its typical characteristics [149,158,162,177,187,[191][192][193][194]. For instance, Malik et al [191] found that the stability of CoPt@Co(OH)2 array can be improved by magnetic field. As a result, the HER LSVs supported by an external magnet showed slight increase in overpotential of 4 mV at a current density of 50 mA cm -2 on the 1st and 5th day of aging.…”
Section: Stabilitymentioning
confidence: 99%